Efficacy of an educational intervention for improving the hydration status of female collegiate indoor-sport athletes - Abbasi, I. S.; Lopez, R. M.; Kuo, Y. T.; Shapiro, B. S. (Journal of Athletic Training, 2021)
Context: Research focusing on improving hydration status and knowledge in female indoor-sport athletes is limited. Investigators have demonstrated that hydration education is an optimal tool for improving the hydration status of athletes. Objective: To assess the hydration status and fluid intake of collegiate female indoor-sport athletes before and after a 1-time educational intervention. Design: Controlled laboratory study. Setting: Collegiate women's volleyball and basketball practices. Patients or Other Participants: A total of 25 female collegiate volleyball and basketball athletes (age = 21 ± 1 years, height = 173.5 ± 8.7 cm, weight = 72.1 ± 10.0 kg) were assessed during 6 days of practices. Intervention(s): Participants' hydration status and habits were monitored for 3 practice days before they underwent a hydration educational intervention. Postintervention, participants were observed for 3 more practice days. Main Outcome Measure(s): Change in body mass, fluid consumed, urine specific gravity (Usg), urine color (Ucol), and sweat rate were recorded for 6 practice days. Participants completed a hydration-knowledge questionnaire before and after the intervention. Results: Three-day mean Usg and Ucol were considered euhydrated prepractice (Usg = 1.015 ± 0.006, Ucol = 4 ± 1) and remained euhydrated postpractice (Usg = 1.019 ± 0.005, Ucol = 5 ± 2) during the preintervention period. Decreased prepractice Ucol (P < .01) and increased hydration knowledge (P < .01) were present postintervention. Basketball athletes had greater body mass losses from prepractice to postpractice than did volleyball athletes (P < .001). Overall increases were evident when we compared prepractice and postpractice measures of Usg and Ucol in the preintervention (P < .001 and P = .001, respectively) and postintervention (P = .001 and P < .001) period, respectively. No correlation was found between hydration knowledge and physiological indices of hydration and fluid intake. Conclusions: Overall, female collegiate indoor-sport athletes were hydrated and knowledgeable on hydration. However, our variable findings indicated that further research on these athletes is needed; clinically, attention should be given to the individual needs of each athlete. More examination will demonstrate whether a 1-time educational intervention may be an effective tool for improving hydration status in this population.